Intercultural Comfort through Social Practices: Exploring Conditions for Cultural Learning - Bernstein, Ruth Sessler; Salipante, Paul (Frontiers in Education, 2017)
High quality cross-ethnic interactions contribute to college students’ development, but knowledge is scant concerning campus settings and conditions that promote these interactions. This study indicates that distinct social practices in particular settings create such conditions. Phenomenological analysis of current and past members of a voluntary community service association (VCSA, a pseudonym), appropriated to meet their social needs, revealed practices leading students from differing ethnic backgrounds to challenge stereotypes and engage in cultural learning. Inductively-derived findings led to a transdisciplinary analysis that synthesizes concepts from institutional (higher education), organizational (voluntary service organization), interpersonal (social ties), and individual (personal development) levels. The emergent concept of intercultural comfort differentiated between meaningful diversity interactions within the student association and apprehensive ones elsewhere. Members experienced this intercultural comfort and an ethnically inclusive moral order due to mission-driven practices emphasizing shared purpose, fellowship, and structured interactions.